O léxico regional de Vidas Secas para o esperanto - Freitas, Edivaldo Simão de (2024)
This research aims to investigate how the lexical choices made by the translator in the translation of Vidas Secas into Esperanto were established in an international version, seeking regional terminological standardization in relation to the original work. A set of entries and neological units selected for the Esperanto version is compared, with the aim of bringing the new entries closer to the original meaning in Portuguese. Our research is based on a number of hypotheses: (i) lexical creation occurs intuitively and naturally; (ii) neologisms are integrated and used by speakers arbitrarily; (iii) Although Esperanto is a planned language, it incorporates neologisms from natural languages, both in speaking and writing; (iv) each new lexical unit contributes dynamically to enriching the language's vocabulary, as can be seen in the translation of Vidas Secas. In addition, we consulted a variety of theorists and scholars, including Saussure, Jakobson, Ricœur, as well as specialists in Esperanto and neologism. Therefore, we aim to contribute to an understanding of translation, lexical evolution and the interaction between natural and planned language, highlighting the dynamic role of language in literature and regional culture.